Anti‐centrosome antibodies: Prevalence and disease association in Chinese population. (23rd July 2019) - Wang, Shengjie; Meng, Yanming; Huang, Zhuochun; Hu, Jing; Niu, Qian; Zhang, Junlong; Yan, Bing; Wu, Yongkang
Abstract: Anti‐centrosome antibodies are rare findings with undefined clinical significance in clinical research. We aimed at investigating the prevalence and clinical significance of anti‐centrosome antibodies in Chinese population. Testing results of total of 281, 230 ANA‐positive sera were retrospectively obtained from West China Hospital Sichuan University in China between 2008 and 2017. We retrospectively collected and analysed the clinical and laboratory data of the patients with positive anti‐centrosome antibody. Of the 356 453 patients tested, 281 230 patients had positive antinuclear antibodies (ANAs, 78.9%), but only 78 patients with positive anti‐centrosome antibodies (0.022%), of which 74.4% are females. Diagnoses were established in 69 of 78 patients: 37 cases were autoimmune diseases, mainly including undifferentiated connective tissue diseases (UCTD, 9/37), rheumatoid arthritis (RA, 6/37), Sjögren's syndrome (SS, 5/37) and primary biliary cirrhosis (PBC, 5/37), and the remaining were other autoimmune conditions. The most frequent clinical symptoms of the anti–centrosome‐positive patients were arthralgia and eyes and mouth drying. Additionally, 86.7% of anti‐centrosome antibodies were not associated with other ANA profiles; however, when associated, the most frequent ANA was anti‐U1RNP. Anti‐centrosome antibodies are featured by a low prevalence and female gender predominance. They are correlated with some specific diseases, both autoimmune diseases, especially UCTD, RA, SS and PBC, and non‐autoimmune diseases, such as infection and cancer, which suggests that they might be potential supporting serological markers of these diseases.